2022
DOI: 10.17113/ftb.60.03.22.7107
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging, Redox Balance and Wound Healing Activity of Bioactive Peptides Derived from Proteinase K-Assisted Hydrolysis of Hypophthalmichthys molitrix Skin Collagen

Abstract: Research background. Various protocols of enzymatic hydrolysis of fish by-products are increasingly tested to ensure value-added products with functional and biological properties important for food, cosmetic and medical applications. In addition, they target to minimize waste from industrial processing and environmental requirements. This study aimed to establish an efficient protocol based on two-step enzymatic hydrolysis of freshwater fish skin and to evaluate the effect of resulted bioactive peptides on fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The studies that we identified reported a variety of benefits; the most frequently reported benefits include • decreased inflammation/inflammatory cells; [35,39] • accelerated wound healing process; [37,43,45] • higher peptide count; [38] • improved wound closure, [35,40,41,45] reduced wound shrinkage, [37] and stronger healed skin; [7] • increased epithelialization, [35,40] migration, [41,42,45] and proliferation [42,44] in wounds;…”
Section: Discussionmentioning
confidence: 99%
“…The studies that we identified reported a variety of benefits; the most frequently reported benefits include • decreased inflammation/inflammatory cells; [35,39] • accelerated wound healing process; [37,43,45] • higher peptide count; [38] • improved wound closure, [35,40,41,45] reduced wound shrinkage, [37] and stronger healed skin; [7] • increased epithelialization, [35,40] migration, [41,42,45] and proliferation [42,44] in wounds;…”
Section: Discussionmentioning
confidence: 99%
“…Other bioeconomy side-streams used as biorefinery feedstock with a high content of minerals are the by-products from chain values based on aquatic organisms. Fish scales and fish bones, which are used to produce collagen hydrolysate with interesting biological properties [42][43][44][45], contain 4.24 ± 0.89% phosphorus and 5.36 ± 1.48% calcium [46] and, respectively, 9.2-9.8% phosphorus and 4.1-4.9% calcium [47].…”
Section: Of 52mentioning
confidence: 99%
“…The second assay is based on the inhibition of the free radicals of DPPH. The inhibition capacity of fluid extracts was analyzed according to an adapted protocol [72]. Briefly, different concentrations of the sample (150 µL) were incubated with 0.25 mM DPPH solution (1.35 mL) and 0.1 M Tris-HCl buffer, pH 7.4 (0.9 mL), at room temperature, in the dark, for 30 min.…”
Section: Determination Of Free Radical Scavenging Capacitymentioning
confidence: 99%